New issues in mediating the Israel-Palestine deadlock - Steiner, Barry H. 1942- (Brill Nijhoff, 2019)
The essays in this book, originally published in a special issue of the journal 'International Negotiation' (vol. 23.1, 2018), are intended to enhance America's ability to mediate Israel-Palestine conflict. Every American president for the last thirty years, down to Donald Trump, has chosen to engage in this effort. To help understand and evaluate these efforts, and to focus upon the more promising mediation directions, these essays analyze mediation options in detail.
Keywords: Vermittlung; Israel; Palästina; Aufsatzsammlung